2022
DOI: 10.1371/journal.pone.0262710
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and practices identification in complex outsourcing relationships: A systematic literature review

Abstract: Complex IT outsourcing relationships aptitude several benefits such as increased cost likelihood and lowered costs, higher scalability and flexibility upon demand. However, by virtue of its complexity, the complex outsourcing typically necessitates the interactions among various stakeholders from diverse regions and cultures, making it significantly more challenging to manage than traditional outsourcing. Furthermore, when compared to other types of outsourcing, complex outsourcing is extremely difficult becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Within the inter-organizational challenges, relationships with several environmental entities such as the insurance system, private partners and customers seemed to be crucial in implementing an efficient process of outsourcing in healthcare units (21,29). Despite the common misconception, one study showed that the relationships between such inter-organizational entities are much more integrated and connected to each other than intra-organizational relationships (30), a finding that clearly states the inter-connected nature of the realm in which any malfunction in the process related to each entity acts like a domino and paves the way for a total failure in the process of service delivery, a phenomenon which was narrated by several studies probing the challenges in the process of outsourcing (27)(28)(29)31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the inter-organizational challenges, relationships with several environmental entities such as the insurance system, private partners and customers seemed to be crucial in implementing an efficient process of outsourcing in healthcare units (21,29). Despite the common misconception, one study showed that the relationships between such inter-organizational entities are much more integrated and connected to each other than intra-organizational relationships (30), a finding that clearly states the inter-connected nature of the realm in which any malfunction in the process related to each entity acts like a domino and paves the way for a total failure in the process of service delivery, a phenomenon which was narrated by several studies probing the challenges in the process of outsourcing (27)(28)(29)31).…”
Section: Discussionmentioning
confidence: 99%
“…As this study foundcomplexities in rural areas as a major inter-organizational challenge faced during the process of outsourcing (29), Some researches have proposed the mainly impoverished low to middle income attribute of the society living in the rural areas as a major contributing factor resulting in an inefficient and ineffective outsourcing process, such phenomenon can be traced back to the fact that after the process of outsourcing which arguably results in higher costs of services for customers, the outsourced units expose to a diminished number of customers due to the lower socioeconomic level of the rural population (32,33); Moreover, staff with higher expertise and higher level of technologies seem to be harder to get employed in rural areas due to the costly nature of such inputs while the outsourced units in the rural areas lack the needed funds and the desired attractiveness to obtain such resources added with the lack of desirability from the side of private partners to cooperate in such risky circumstances (23,27). Some studies have found lack of negotiating power as a major challenge ahead of organizations daring to outsource some of their units leading to a complete dependency to the private partner which ultimately results in the inability of the outsourced units to preserve its interests and desired targets (21,(27)(28)(29); this phenomenon has shown to be the result of multiple circumstances such as insufficiency of private partners, disparities with the insurance system due to the existing conflict of interests and more importantly the inconvenient structure of the draft and the inability and lack of expertise to design and propose a comprehensive draft in the process of outsourcing (21,22,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outsourcing refers to the transfer of activities to external parties. Although both internal and external activities create value for the client, sometimes it is more efficient for the organization to externalize some non-core activities to parties who can provide the required services faster and cheaper [80][81][82].…”
Section: Outsourcingmentioning
confidence: 99%
“…Each development team in GSD is responsible to develop their own component with little concentration on the full picture of the whole system. 2,11,13,27,28,41 Similarly, each team may be using a dissimilar process model and standards that will further complicate the integration process at the end. 10,42 In GSD, a late consideration on the integration problem may make the project more problematic and may increase the overall development cost.…”
Section: Introductionmentioning
confidence: 99%